Chaperone-like activity of peptidyl-prolyl cis-trans isomerase during creatine kinase refolding - Ou, Wen-Bin (Cold Spring Harbor Laboratory Press, 2001)
Porcine kidney 18 kD peptidyl-prolyl cis-trans isomerase (PPIase) belongs to the cyclophilin family that is inhibited by the immunosuppressive drug cyclosporin A. The chaperone activity of PPIase was studied using inactive, active, and alkylated PPIase during rabbit muscle creatine kinase (CK) refolding. The results showed that low concentration inactive or active PPIase was able to improve the refolding yields, while high concentration PPIase decreased the CK reactivation yields. Aggregation was inhibited by inactive or active PPIase, and completely suppressed at 32 or 80 times the CK concentration (2.7 μM). However, alkylated PPIase was not able to prevent CK aggregation. In addition, the ability of inactive PPIase to affect CK reactivation and prevent CK aggregation was weaker than that of active PPIase. These results indicate that PPIase interacted with the early folding intermediates of CK, thus preventing their aggregation in a concentration-dependent manner. PPIase exhibited chaperone-like activity during CK refolding. The results also suggest that the isomerase activity of PPIase was independent of the chaperone activity, and that the proper molar ratio was important for the chaperone activity of PPIase. The cysteine residues of PPIase may be a peptide binding site, and may be an essential group for the chaperone function.